Acesso e produção acadêmica de estudantes cotistas negros da Universidade Federal do Maranhão - Maciel, Regimeire Oliveira (2014)
Affirmative action in higher education in Brazil are the main feature of studies and research on race relations in the country .Quotas and yours repercussions , have offered new elements to these studies and in-depth some that have been commonly addressed. The academic production of students who came from these initiatives, illustrate this aspect properly. In this work we aimed to discuss the motivations and guiding elements of the academic production of black quotist students of the Federal University of Maranhao (UFMA). The data indicate that two sets of factors act to manifest the interest surrounding this production. Pre-college life experiences, considering the conditions faced to access higher education, and those found internally, arise as influences on reports of students interviewed, especially when asked about what they want to produce in the academic realm